Novel layered double hydroxide chemistry for application in cement and other building materials - Wongariyakawee, A (2013)
The investigation into the syntheses and the intercalations of LDHs is the focus of the work described in this thesis. An introduction to Layered Double Hydroxide (LDH) materials with an emphasis on the possible host lattices and to their applications is given in Chapter 1. The application of LDHs in cement including; history of cement, cement production process, and cement hydration is detailed. The synthesis of the Ga-doped Ca2Al(OH)6Cl•nH2O LDHs (Ca2GaxAl(1–x)-Cl; where 0 < x < 1) via the co-precipitation method is reported in Chapter 2. The effect of doping Ga3+ on a parameter of Ca2GaxAl(1–x)-Cl was determined by using Vegard’s law and the correlation between a parameter and x value was derived. The intercalation of organic anions including; sodium styrene sulfonate, sodium butene dicarboxylate, sodium fumarate and ammonium poly(styrene sulfonate), in Ca2Ga-Cl structure is described. The intercalation of lignosulfonate, naphthalene sulfonate and polycarboxylate into Ca2Al(OH)6NO3·6H2O (Ca2Al-NO3) is detailed in Chapter 3. The release behaviour for the LDHs and the kinetic modelling of the release are reported. The effects of these LDHs on cement hydration studied by using the in situ X-ray diffraction and the ultrasound shear-wave reflection are discussed. In Chapter 4, the synthesis of Ca2Al(OH)6NO3·nH2O via a non-ionic surfactant reverse microemulsion is reported. The effects of the amount and the solubility [Hydrophile-Lipophile Balance (HLB)] of non-ionic surfactant on the morphology and the size distribution of the LDHs are discussed. Two new nitrite intercalated Ca2Al-LDHs [Ca2Al(OH)6NO2·nH2O] synthesised via both the co-precipitation and the reverse micro-emulsion method are detailed in Chapter 5. The hydration of Portland cement samples with additive nitrate- and nitrite-intercalated Ca2Al-LDH made using co-precipitation is discussed. The synthesis of dispersed, uniform nanoplatelet [Ca2Al(OH)6DDS]•H2O LDHs is reported in Chapter 6. The effects of the amount of the surfactant on the morphology and size distribution of the LDHs are described. The experimental procedures and characterising techniques employed in this study are listed in Chapter 7. Additional data are provided in the Appendices.